Imaging the electric potential within organic solar cells - Saive, Rebecca; Scherer, Michael; Müller, Christian; Daume, Dominik; Schinke, Janusz; Kroeger, Michael; Kowalsky, Wolfgang (Advanced functional materials, 2013)
The charge transport in organic solar cells is investigated by surface potential measurements via scanning Kelvin probe microscopy. Access to the solar cell's cross-section is gained by milling holes with a focused ion beam which enables the direct scan along the charge transport path. In a study of poly(3-hexylthiophene):1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]C61 (P3HT:PCBM) bulk heterojunction solar cells, the open circuit voltage is built up at the top contact. A comparison of the potential distribution within normal and inverted solar cells under operation exhibits strongly different behaviors, which can be assigned to a difference in interface properties.
Gesehen am 26.01.2022